Improvement of Performance Management and Rewards System in a Non-Profit Organization in Indonesia - Rif’ah Shofia; Aurik Gustomo (Eduvest - Journal of Universal Studies, 2025)
This paper analyses the current Performance Management and Rewards system in a non-profit organization in Indonesia that is undergoing significant change and aims to achieve its ambitious goals in the next 5 years. This research utilizes primary data in the form of interviews with staff in various positions in the organization, and secondary data in the form of organizational documents, employing qualitative methodology with thematic analysis. To evaluate the effectiveness of the current system, established frameworks from previous researches were used, with slight modifications to align with the organizational environment as a nonprofit organization. The results indicate several critical gaps, such as a lack of rewards differentiation for high performance, concerns with the current “rating-less evaluation” approach, and a lack of goal alignment within organization and between individual and organizational goals. The comprehensive improvements proposed are ensuring goal alignment, incorporating SMART KPIs (Specific, Measurable, Achievable, Relevant, and Time-bound), enhancing training for managers and everyone in the organization, equipping managers and evaluators to be able to carry-out performance evaluations, applying a rating-based evaluation approach, and pay-for-performance schemes to differentiate rewards based on performance.